If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -23 = -7 + 2x Reorder the terms: -23 + 6x = -7 + 2x Solving -23 + 6x = -7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -23 + 6x + -2x = -7 + 2x + -2x Combine like terms: 6x + -2x = 4x -23 + 4x = -7 + 2x + -2x Combine like terms: 2x + -2x = 0 -23 + 4x = -7 + 0 -23 + 4x = -7 Add '23' to each side of the equation. -23 + 23 + 4x = -7 + 23 Combine like terms: -23 + 23 = 0 0 + 4x = -7 + 23 4x = -7 + 23 Combine like terms: -7 + 23 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| x^9+y^6=36 | | (x^2/25)^1/2 | | 0.5714=0.08333x | | 2=200/x^2 | | n-m=6 | | 4/7=x/12 | | x^2+y^2+2x-16y=16 | | (2x+7)=(3x+3) | | x/7=63/x | | 17-4(6x-2)=-3 | | 3x^2+10x-13=17-3x | | 2x^2+15x= | | 8c^4/-8a^3b^9c^4 | | 5x^2y/12xy^5•2x^5y^3/4x^4y^4 | | 4/9(K-4/7) | | 2x-7-39=0 | | a^2(b-8)-9(b-8)= | | b-10=180 | | 10-x/3x^2 | | 16(v+2)-4v=4(3v+1)-7 | | -10-60= | | 5x-10/x^2-2x= | | 400=5+15x | | 400=80-10x | | 400=925-5x | | 2x+5(-1)=-19 | | 8-2*5+2= | | 2m^2=-28 | | 4*2+6-5= | | x^2+9x-87=3 | | 5y-4=7+10y | | 1-3ln(x)=11 |